2017
DOI: 10.1073/pnas.1704199114
|View full text |Cite
|
Sign up to set email alerts
|

Size and mobility of lipid domains tuned by geometrical constraints

Abstract: In the plasma membrane of eukaryotic cells, proteins and lipids are organized in clusters, the latter ones often called lipid domains or "lipid rafts." Recent findings highlight the dynamic nature of such domains and the key role of membrane geometry and spatial boundaries. In this study, we used porous substrates with different pore radii to address precisely the extent of the geometric constraint, permitting us to modulate and investigate the size and mobility of lipid domains in phase-separated continuous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 61 publications
6
42
0
Order By: Relevance
“…At this stage, l b -or l o -domains become discernible, even though the time resolution was not sufficient to resolve the circular appearance of such domains in the f-PSMs that we have visualized previously. 44 Circular domains are indicative of a significant line tension, which has been determined by Schwille and coworkers for a similar lipid composition (DOPC/SM C 18:0 /Chol, 2 : 2 : 1) to be 1.2 pN. 60 Tsai and Feigenson 61 later demonstrated that an increase in the Chol content slightly reduces the line tension in such membrane mixtures.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…At this stage, l b -or l o -domains become discernible, even though the time resolution was not sufficient to resolve the circular appearance of such domains in the f-PSMs that we have visualized previously. 44 Circular domains are indicative of a significant line tension, which has been determined by Schwille and coworkers for a similar lipid composition (DOPC/SM C 18:0 /Chol, 2 : 2 : 1) to be 1.2 pN. 60 Tsai and Feigenson 61 later demonstrated that an increase in the Chol content slightly reduces the line tension in such membrane mixtures.…”
Section: Resultsmentioning
confidence: 77%
“…19,[33][34][35][36][37][38][39][40][41][42] As yet, PSMs composed of PC/SM/Chol have been formed on gold functionalized pore rims, and hence, owing to the quenching of the fluorescence by the gold layer, s-PSMs could not be fluorescently observed lacking the information about l o /l d -phase separation of the entire PSM. 43,44 To overcome this drawback, we here make use of SiO x=1-2 functionalized porous silicon substrates 33 in combination with two fluorescent (l d -and l o -) markers allowing the visualization of f-PSMs and s-PSMs. Our results on DOPC/ SM/Chol PSMs with different Chol contents highlight the importance of the differences in adhesion of particular membrane lipids considerably altering the phase behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The PSM is a membrane with two different areas (s-PSMs and f-PSMs), in which the membrane components diffuse differently (30,31). Moreover, at the boundary of s-PSM and f-PSM, the membrane is locally bent (29). It is conceivable that the topography of the PSM also influences the diffusion behavior.…”
Section: And the Larger Viscosity Of The Cytosolmentioning
confidence: 99%
“…To overcome the drawback of fully immobile docked vesicles and to observe possible intermediate fusion states by fluorescence microscopy in a time-resolved manner, we used planar pore-spanning membranes (PSMs) (28,29). These membranes consist of freestanding PSM (f-PSM) and supported PSM (s-PSM) areas and thus allow a comparison of the diffusive and fusion behavior of docked vesicles on the two different membrane types under otherwise exact same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic growth and development mechanisms also depend on diffusion, as does tumor growth and metastasis. Adsorbed liposomes onto structured surfaces can form fluid, supported lipid bilayers as realistic models for biomembranes capable of mimicking cellular functions such as transport and signaling . Micro‐ and nanopatterned surfaces can be utilized to mimic the geometries and scales of these environments, and to elucidate how biological phenomena that rely on diffusive transport are impacted in these spatially restricted environments …”
Section: Introductionmentioning
confidence: 99%